The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m601960200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Clustered Phosphocholine Head Groups Serve as Sites for Binding and Assembly of an Oligomeric Protein Pore

Abstract: High susceptibility of rabbit erythrocytes toward the poreforming action of staphylococcal ␣-toxin correlates with the presence of saturable, high affinity binding sites. All efforts to identify a protein or glycolipid receptor have failed, and the fact that liposomes composed solely of phosphatidylcholine are efficiently permeabilized adds to the enigma. A novel concept is advanced here to explain the puzzle. We propose that low affinity binding moieties can assume the role of high affinity binding sites due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
111
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 43 publications
(34 reference statements)
8
111
0
2
Order By: Relevance
“…Recently, a new concept has been proposed to explain the binding of alpha-toxin, another member of the family of staphylococcal pore-forming toxins which forms homotypic heptamers. Besides low-affinity binding sites, the role of high-affinity receptors for this toxin would be played by clusters of phosphocholine head groups in sphingomyelin-cholesterol-rich microdomains (20) and consequently would not be protein mediated. The present study did not result in any final conclusions concerning the receptors of bicomponent leukotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new concept has been proposed to explain the binding of alpha-toxin, another member of the family of staphylococcal pore-forming toxins which forms homotypic heptamers. Besides low-affinity binding sites, the role of high-affinity receptors for this toxin would be played by clusters of phosphocholine head groups in sphingomyelin-cholesterol-rich microdomains (20) and consequently would not be protein mediated. The present study did not result in any final conclusions concerning the receptors of bicomponent leukotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Such small clusters of cholesterol could serve as docking sites for LLO and facilitate oligomerization, as shown by our results. Clustered lipids as binding sites for proteins emerge as a general concept in PFT; i.e., the binding and permeabilizing activity of ostreolysin, a PFT from oyster mushroom, is optimal above 40% cholesterol in sphingomyelin-containing membranes (61), and Valeva et al have recently shown that clustered phosphocholine headgroups lead to rapid oligomerization of staphylococcal R-toxin (62).…”
Section: Discussionmentioning
confidence: 99%
“…This feature is not unique to HlyA, as the sensitivity to other poreformers such as ␣-toxin from Staphylococcus aureus also shows great interspecies variability (7). Regarding S. aureus, the interspecies variation was explained through differences in expression levels of a specific receptor for ␣-toxin (8). This option has also been suggested for HlyA-induced hemolysis (9) but is not yet generally accepted (10).…”
mentioning
confidence: 99%